2015
DOI: 10.1159/000369251
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Possible Role of Kir4.1 and Kir5.1 in Thyroid Hormone Biosynthesis

Abstract: Introduction: Thyroid morphogenesis is a complex process. Inwardly rectifying potassium (Kir) genes play a role in hormone release, cell excitability, pH and K+ homeostasis in many tissues. Objectives: To investigate the thyroid developmental expression of three members, Kir4.1, Kir4.2 and Kir5.1, in mice. To postulate the K+ channel role in thyroid hormone secretion. Material and Methods: Quantitative RT-PCR analysis of Kir4.1, Kir4.2 and Kir5.1 in mice of different stages (E13.5-E18.5).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Inwardly rectifying K + (Kir) channels belong to a large family of potassium channels which comprises seven subfamilies (Kir1.x–Kir7.x) that are abundantly expressed and show distinctive features in many different tissues and cell types, such as kidney epithelial cells (Kir1.1/KCNJ1, or renal outer medullary potassium channel ROMK1 52 ); cardiac myocytes (Kir2.x, Kir3.x, and Kir6.x channels 53 ); brain cortical neurons and glia cells (various members of the Kir2, Kir3, Kir4, and Kir6 subfamilies 54 ); thyroid epithelial cells (Kir 5.1/KCNJ16 55 ); and pancreatic β cells (Kir6.1/KCNJ8 and Kir6.2/KCNJ11 56 ). Due to the intrinsic properties of the open‐channel pore as well as an asymmetric open‐channel pore block by intracellular divalent cations and polyamines, Kir channels facilitate a greater influx of potassium ions rather than an efflux—the so‐called inward rectification.…”
Section: Discussionmentioning
confidence: 99%
“…Inwardly rectifying K + (Kir) channels belong to a large family of potassium channels which comprises seven subfamilies (Kir1.x–Kir7.x) that are abundantly expressed and show distinctive features in many different tissues and cell types, such as kidney epithelial cells (Kir1.1/KCNJ1, or renal outer medullary potassium channel ROMK1 52 ); cardiac myocytes (Kir2.x, Kir3.x, and Kir6.x channels 53 ); brain cortical neurons and glia cells (various members of the Kir2, Kir3, Kir4, and Kir6 subfamilies 54 ); thyroid epithelial cells (Kir 5.1/KCNJ16 55 ); and pancreatic β cells (Kir6.1/KCNJ8 and Kir6.2/KCNJ11 56 ). Due to the intrinsic properties of the open‐channel pore as well as an asymmetric open‐channel pore block by intracellular divalent cations and polyamines, Kir channels facilitate a greater influx of potassium ions rather than an efflux—the so‐called inward rectification.…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis requires further investigation. The Kir4.1, Kir4.2, Kir5.1 mRNA levels had significantly increased during mouse thyroid gland development [13]. Targeting Kir5.1 may be a promising strategy for patients with an RAIR status.…”
Section: Kir51 In Thyroid Cancermentioning
confidence: 95%
“…Kir5.1 (encoded by KCNJ16) is the only identified member of the Kir5.x subfamily. Kir5.1 mRNA has been identified in several important organs, such as the brain, thyroid, parathyroid gland, kidney, liver, testis, and adrenal glands as a K+ transport channel [10][11][12][13]. Generally, a functional Kir channel is a tetrameric complex that can be either homomeric or heteromeric.…”
Section: Kir51 In Thyroid Cancermentioning
confidence: 99%
“…At present, studies on Kir5.1 and cancer mainly focus on the thyroid, pancreas, and prostate, among others, and the expression changes of Kir5.1 are not consistent in different glands during carcinogenesis (Table 1). In 2014, Ramos et al found that Kir5.1, Kir4.1, and Kir4.2 were significantly expressed in the thyroid, but the function of Kir5.1 in the thyroid was unclear, although it was suggested to be involved in the transport of thyroglobulin (Ramos et al, 2015). Liu et al analyzed mRNA datasets from 23 anaplastic thyroid cancer (ATC) samples and 24 normal samples and identified 55 differentially expressed genes (DEGs).…”
Section: Kir51 and Cancermentioning
confidence: 99%